Bovine Respiratory Disease (BRD) Complex as a Signal for Bovine Viral Diarrhea Virus (BVDV) Presence in the Herd - Basqueira, Natália Sobreira; Martin, Camila Cecilia; Costa, Juliana França dos Reis; Okuda, Líria Hiromi; Pituco, Maristela Edviges; Batista, Camila Freitas; Libera, Alice Maria Melville Paiva Della; Gomes, Viviani (Acta Scientiae Veterinariae, 2017)
Background: Infections are caused by Bovine Viral Diarrhea Virus and still continue to be a worldwide plague in cattle industry. It is responsible for sudden death syndromes in adult cattle with high mortality rates, abortions, acute gastrointestinal and respiratory diseases. The BVDV infection occurs in early pregnancy (40-142 days), in immunosuppressed females or cows results in 100% of persistently infected (PI) calves that are seronegative and asymptomatic at birth. Evidences suggests that BVDV contributes to BRD complex potentiating secondary infections caused by Mannheimia haemolytica e Pasteurella multocida due to its immunosuppressive action. However, the farmers have often associated the respiratory syndrome with other infectious agents. This paper reports the attendance of dairy calves manifesting clinical signs of bronchopneumonia, which led to the screening of the persistently infected animals to control of the BVDV infection in the herd. Materials, Methods & Results: During the technical assistance, ten calves manifesting bronchopneumonia were selected to trans-tracheal lavage (TL) in order to identify possible infectious agents. Reverse transcription polymerase chain reaction (RT-PCR) detected the presence of BVDV in two heifers. Pasteurella multocida was the unique bacterial agent isolated from TL (5/10, 50%). These data motivated the technical team and producers to investigate the PI screening by direct enzyme-linked immunosorbent assay from biopsies of the ear edge. The screening of PI’s detected 29 positive within of 2,342 animals tested (1.23%). The re-test of positive was performed only in 24 animals due to the cull of five bovine with severe bronchopneumonia and diarrhea, confirming 18 persistently infected calves (18/24; 75%). Finally, in all PI’s live dams were tested. It was observed four positive adult animals. One grand dam was live and tested, but it had negative result for direct enzyme-linked immunosorbent test. The rate of PI’s considering the whole herd was 0.81% (22/3,700 animals). Discussion: The involvement of BVDV in the etiology of bronchopneumonia was confirmed by detection of the virus in trans-tracheal lavages in two calves by RT-PCR. The susceptibility for Pasteurella multocida infection could be promoted by BVDV prime-infection, considering that immunossupressive nature of BVDV is a critical factor in the interaction with others viruses and bacteria. At this time, we are aware about any report about the detection of BVDV in trans-tracheal lavages. These findings culminated with the screening of PI animals in the herd, detecting rates of 0.81%. The intensive vaccination and colostrum management of this farm could protected the herd against BVDV, however others facts facilitated the introduction of the virus in the herd. This research was conduced in a high-production dairy farm with around 3,700 animals raised in an open herd, in which some of cows with high genetic potential were transferred for embryo collection in the state of Paraná, Brazil; resulting in the addition of the calves to the herd by others routes. Moreover, the farm used for many years vaccine containing only BVDV-1, which may have favored the entry and spread of BVDV-2 or BVDV-3 in the herd. This research showed the presence of BVDV in trans-tracheal lavage of heifers with bronchopneumonia by RT-PCR. This fact points to the need of BRD control programs that include detection of PI animals.